The relationship between renewable energy consumption and economic growth in Serbia - Kalaš Branimir; Mirović Vera; Pavlović Nataša (Trendovi u Poslovanju)
Renewable energy plays a vital role in achieving sustainable growth that entails economic development that meets the needs of the present generation without compromising the ability of future generations to meet their own needs. The study analyzes the relationship between renewable energy consumption and economic growth in Serbia for the period of 2006-2020. Empirical results indicate a positive effect of renewable energy consumption on economic growth, as well as a unidirectional causality between these variables. The findings confirm that higher renewable energy consumption contributes to greater economic growth rates.